Soyasaponin I alleviates hypertensive intracerebral hemorrhage by inhibiting the renin–angiotensin–aldosterone system. (31st December 2023) - Li, Wei; Li, Shao-Guang; Li, Lan; Yang, Li-Jian; Li, Zeng-Shi; Li, Xi; Ye, An-Yuan; Xiong, Yang; Zhang, Yi; Xiong, Yuan-Yuan
ABSTRACT: Background: Hypertensive intracerebral hemorrhage (HICH) is a life-threatening disease and lacks effective treatments. Previous studies have confirmed that metabolic profiles altered after ischemic stroke, but how brain metabolism changes after HICH was unclear. This study aimed to explore the metabolic profiles after HICH and the therapeutic effects of soyasaponin I on HICH. Methods: HICH model was established first. Hematoxylin and eosin staining was used to estimate the pathological changes after HICH. Western blot and Evans blue extravasation assay were applied to determine the integrity of the blood–brain barrier (BBB). Enzyme-linked immunosorbent assay was used to detect the activation of the renin–angiotensin–aldosterone system (RAAS). Next, liquid chromatography–mass spectrometry-untargeted metabolomics was utilized to analyze the metabolic profiles of brain tissues after HICH. Finally, soyasaponin I was administered to HICH rats, and the severity of HICH and activation of the RAAS were further assessed. Results: We successfully constructed HICH model. HICH significantly impaired BBB integrity and activated RAAS. HICH increased PE(14:0/24:1(15Z)), arachidonoyl serinol, PS(18:0/22:6(4Z, 7Z, 10Z, 13Z, 16Z, and 19Z)), PS(20:1(11Z)/20:5(5Z, 8Z, 11Z, 14Z, and 17Z)), glucose 1-phosphate, etc., in the brain, whereas decreased creatine, tripamide, D-N-(carboxyacetyl)alanine, N-acetylaspartate, N-acetylaspartylglutamic acid, and so on in the hemorrhagic hemisphere. Cerebral soyasaponin I was found to be downregulated after HICH and supplementation of soyasaponin I inactivated the RAAS and alleviated HICH. Conclusion: The metabolic profiles of the brains changed after HICH. Soyasaponin I alleviated HICH via inhibiting the RAAS and may serve as an effective drug for the treatment of HICH in the future.